Skor assessment of different neoplasias in the adnexa (ADNEX) untuk memprediksi keganasan ovarium di RSUP Sanglah Denpasar - I Nyoman Gede Budiana; Ketut Suwiyoga; Tjokorda Gde Agung Suwardewa; Anom Suardika; Made Bagus Dwi Aryana; Heni Sunyoto (Intisari Sains Medis, 2022)
Introduction: Ovarian cancer is cancer of the female reproductive organs with the highest mortality and is in the third position of female cancer after mammary and cervical cancer. The mortality rate and survival rate of ovarian cancer is mainly determined by the stage at which ovarian cancer is diagnosed. Until now there is no method for early detection of ovarian cancer with good sensitivity and specificity. Assessment of different neoplasias in the adnexa (ADNEX) is a model proposed by international ovarian tumor analysis (IOTA) to help distinguish benign or malignant adnexa tumors.Methods: This study is a observational clinical test to find out the accuracy of ADNEX model to predict ovarian malignancy conducted at the Obstetric and Gynecology Outpatient Ward in Sanglah hospital, Denpasar from November 2019 to April 2020. Consecutive sampling was done and 88 sample was recruited with a diagnosis of ovarian tumors. Then the research sample was sent to the Pathology Anatomy laboratory of Sanglah Hospital for histopathological examination. This result would then be compared to the prediction results of the ADNEX model.Results: 35 samples of benign ovarian tumors and 53 samples of ovarian cancer were found with the ADNEX method. There were 46 samples with malignant tumor both by the ADNEX model and histopathology results, 7 samples of malignant tumor at histopathology result but benign by the ADNEX model, 6 samples of benign tumor according to histopathology but malignant using the ADNEX model, and 29 samples of benign tumor according to histopathology and the ADNEX model. Using cut off of 49,6%, the study reported a sensitivity level of 86.8%, specificity 82.6%, positive predictive value 88.5%, negative predictive value 80.6%, and 85.2% accuracy.Conclusion: The ADNEX model has a high level of specificity, sensitivity and diagnostic accuracy in diagnosing ovarian cancer and can be used in combination with other clinical markers for early detection of malignancy in ovarian tumors.  Pendahuluan: Kanker ovarium merupakan salah satu jenis kanker organ reproduksi wanita dengan mortalitas tertinggi dan berada pada posisi ke-tiga kanker perempuan setelah kanker mammae dan serviks. Angka mortalitas dan survival rate kanker ovarium sangat ditentukan oleh stadium saat kanker ovarium terdiagnosis. Hingga saat ini belum tersedia metode pemeriksaan untuk deteksi dini kanker ovarium dengan sensitivitas dan spesifisitas yang memadai. Assessment of different neoplasias in the adnexa (ADNEX) adalah model yang diajukan oleh International Ovarian Tumor Analysis (IOTA) untuk membantu membedakan tumor adnexa sebagai tumor jinak atau ganas. Metode: Penelitian ini merupakan penelitian observasional uji klinik untuk mengetahui akurasi model ADNEX untuk memprediksi keganasan ovarium yang dilakukan di Poliklinik Kebidanan dan Penyakit Kandungan RSUP Sanglah, Denpasar pada bulan November 2019 hingga April 2020. Sampling dilakukan secara consecutive dan didapatkan 88 orang dengan diagnosis tumor ovarium. Sampel penelitian dikirimkan ke laboratorium Patologi Anatomi RSUP Sanglah dan dilakukan pemeriksaan histopatologi untuk kemudian dibandingkan dengan hasil prediksi dari model ADNEX.Hasil: Dalam penelitian ini didapatkan 35 sampel dengan tumor jinak ovarium dan 53 sampel dengan kanker ovarium dengan menggunakan metode ADNEX. Terdapat 46 sampel dengan hasil pemeriksaan model ADNEX ganas dan hasil pemeriksaan histopatologi ganas, 7 sampel histologi ganas namun model ADNEX jinak, 6 sampel histopatologi jinak namun model ADNEX ganas, dan 29 sampel histopatologi jinak dan model ADNEX jinak. Hasil penelitian memperlihatkan tingkat sensitifitas 86,8%, spesifisitas 82,6%, nilai prediksi positif 88,5%, nilai prediksi negatif 80,6%, dan akurasi 85,2%.Simpulan: Model ADNEX memiliki tingkat spesifisitas, sensitivitas dan akurasi diagnostik yang tinggi dalam mendiagnosis kanker ovarium dan dapat digunakan bersama dengan penanda klinis lain untuk deteksi dini keganasan pada tumor ovarium.